Association of exposure to Bisphenol A with obesity and cardiometabolic risk factors in children and adolescents. Issue 1 (2nd January 2019) - Amin, Mohammad Mehdi; Ebrahim, Karim; Hashemi, Majid; Shoshtari-Yeganeh, Bahareh; Rafiei, Nasim; Mansourian, Marjan; Kelishadi, Roya
ABSTRACT: In this study, the association of exposure to Bisphenol A (BPA) with obesity and cardiometabolic risk factors was investigated on 132 children and adolescents aged 6–18 years living in Isfahan, Iran. Potential contributors to BPA exposure were assessed by a questionnaire. Total BPA was detected in urine samples of all participants without significant difference in boys and girls. The mean body mass index (BMI) and waist circumference (WC) increased significantly across the BPA tertiles ( p for trend = < 0.001). Similar trend was documented for systolic blood pressure (SBP) and diastolic blood pressure (DBP) as well as fasting blood sugar. The risk of obesity was 12.48 times higher in participants in the third tertile of BPA than in others (95% CI: 3.36–46.39, p  < 0.001). The current study showed significant association between BPA exposure with obesity and some cardiometabolic risk factors in children and adolescents, however, further longitudinal studies are necessary to evaluate the clinical effects of this finding. Abbreviations: BMI: Body Mass Index; BPA: Bisphenol A; BSTFA: N, O-Bistrifluoroacetamide; CDC: Centers for Disease Control and Prevention; CI: Circumference Interval; DBP: Diastolic Blood Pressure; DLLME: Dispersive liquid-liquid microextraction method; FBS: Fasting Blood Glucose; HDL: high-density lipoprotein cholesterol were; LDL: low-density lipoprotein cholesterol; OR: Odd Ratio; PA: Physical Activity; SBP: Systolic Blood Pressure; TC: total cholesterol; TG: triglycerides; WC: Waist Circumference.